Valine 11 and phenylalanine 13 have a greater impact on the T-cell response to citrullinated peptides than the 70–74 shared epitope of the DRB1 molecule in macaques. Issue 7 (25th April 2019) - Bitoun, Samuel; Roques, Pierre; Maillere, Bernard; Le Grand, Roger; Mariette, Xavier
Abstract : Objectives: Various rheumatoid arthritis (RA) HLA-DRB-1 risk haplotypes have been regrouped under the shared epitope (SE) in position 70–74. The presence of Valine in position 11 (Val11) and phenylalanine in position 13 (Phe13) are also associated with RA, but it is impossible to differentiate their role compared with the SE since they are in strong linkage disequilibrium (LD) in humans. Similar to humans, certain macaques express the SE (H6). We analysed the effect of various DRB1 haplotypes on T-cell response to citrullinated peptides (Cit-P) in macaques. Methods: Six H6 and six non-H6 macaques were immunized with four Cit-P. T-cell response was assessed using Interferon γ enzyme-linked immunospot. Results: Animals developed a specific anti-Cit-P T-cell response. Surprisingly, H6 animals had a significantly lower T-cell response than non-H6. In macaques, the 70–74 SE and the Val11 are on separate haplotypes. Presence of Val11 was strongly associated with the anti-Cit-P T-cell response, whatever the 70–74 sequence was. This response was amplified in case of presence of Phe13. Conclusion: The absence of LD between Val11 and SE in macaques allowed us to demonstrate that the most important HLA positions to induce a T-cell response against Cit-P were Val11 and Phe13 and not the 70–74 SE.